The Association Between Certain Immunological Markers And Clinical Manifestation Of SLE In Iraqi Arab Patients (Journal of the College of Basic Education, 2023)
The present study was conduction to have a clearer integrative ideaon the impact of immunological abnormalities including a set of autoantibodies on the clinical expression of lupus among Iraqi Arab patients,compared with a normal population matched in ethnic background. Atotal of (39) well diagnosed patients with lupus attending therheumatology clinic of medical city in Baghdad (from Jun – 2005 toOctober – 2006) have been studied compared with (40) normalindividuals of a blood bank donors as a general control. Indirect immunofluorescent technique was used to assess theprevalence of antinuclear antibody among subjects group, while otherauto antibodies including anti – ds DNA, anti – Sm, anti – Ro, anti – La,anti – Sm RNP, and anti- cardiolipin antibodies were detected withenzyme immuno assay (EIA) and rheumatoid factor with latexagglutination. Patient's group reported prevalence of all the eight seroimmunological abnormalities in a statistically significant way, comparedto general control. The risk for having a positive immunological markerfor cases (represented by odds ratio) ranged between (7.5) forrheumatoid factor to (61.2) for antinuclear antibodies. Besides, selectedauto antibodies were significantly associated with particularmanifestation. Patients testing positive for rheumatoid factor had asignificant risk of having malar rush (OR = 11.0 , P < 0.05) and thosehow had positive results for anti – ds DNA and anti – Sm antibodies had asignificant risk of having renal involvement (OR = 4.7 and 4.3respectively , P < 0.05) , while having anti – Ro antibodies decrease therisk of developing arthropathy (OR=0.2, P < 0.05). Nonetheless,